Bergey's Manual of Systematics of Archaea and Bacteria 2015
DOI: 10.1002/9781118960608.gbm00928
|View full text |Cite
|
Sign up to set email alerts
|

Bordetella

Abstract: Bor.de.tel' la . M.L. dim ending ‐ ella; M.L. fem. n. Bordetella named after Jules Bordet, who with O. Gengou first isolated the organism causing pertussis. Proteobacteria / Betaproteobacteria / Burkholderiales / Alcaligenaceae / Bordetella Minute coccobacillus, 0.2–0.5 µm in diameter and 0.5–2.0 µm in length, often bipolar stained, and arranged singly or in pairs, more rarely in chains. Gram negative. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 117 publications
0
1
0
Order By: Relevance
“…The presence of Bordetella in ST deserves to be discussed in detail. Bordetella species were mainly isolated from warm-blooded animals (including humans) and, until recently, they were thought to be only animal pathogens [ 63 , 64 ]. Nonetheless, recent studies revealed that Bordetella strains could also have an environmental origin [ 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of Bordetella in ST deserves to be discussed in detail. Bordetella species were mainly isolated from warm-blooded animals (including humans) and, until recently, they were thought to be only animal pathogens [ 63 , 64 ]. Nonetheless, recent studies revealed that Bordetella strains could also have an environmental origin [ 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%